2014
DOI: 10.4103/2249-4863.148107
|View full text |Cite
|
Sign up to set email alerts
|

Study of general awareness, attitude, behavior, and practice study on dog bites and its management in the context of prevention of rabies among the victims of dog bite attending the opd services of chc muradnagar

Abstract: Objectives:This is a recent study conducted during 15th September 2013 to 15th December 2013 at the community health centre (CHC), Muradnagar, distt Ghaziabad, among the victims of dog/animal bite attending the daily OPD services of CHC. To identify the level of general awareness and knowledge of wound management and rabies among the cases of dog bite and to study the awareness of people about antirabies vaccines and health service utilization.Methods:The study population composed of 250 victims of dog or anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 2 publications
7
23
1
Order By: Relevance
“…On the similar lines to our results, both Jain et al and Singh et al found very low level of awareness about the post dog bite management of wounds. 7,8 But in contrary to our results, two other studies showed that more than three fourth of animal bite victims were found to have sufficient knowledge of the same. 9,10 These differences in the findings could be attributed to education status of victims Time interval between bite and initiation of wound washing is critical in prevention of rabies.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…On the similar lines to our results, both Jain et al and Singh et al found very low level of awareness about the post dog bite management of wounds. 7,8 But in contrary to our results, two other studies showed that more than three fourth of animal bite victims were found to have sufficient knowledge of the same. 9,10 These differences in the findings could be attributed to education status of victims Time interval between bite and initiation of wound washing is critical in prevention of rabies.…”
Section: Discussioncontrasting
confidence: 56%
“…But Jain et al and Kumar et al reported 18% and 55% of cases respectively were aware about the fatality rate (100%) of the disease once occurred. 7,9 In our study, victims also did not have the desired information regarding symptoms of rabies. This could be because of low education status of victims as out of the 59 victims who were unaware of the fatality of rabies majority (around 86%) were educated only upto XII class.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Another study conducted in Kolkata reported that maximum number of study participants reported to health center within 24 to 48 hours and very few cases within 24 hours after bite. Late reported cases, especially after 5 days, constituted by younger children or illiterate elderly people were forcefully brought to the hospital by their family members or caregivers.…”
Section: Discussionmentioning
confidence: 99%